Design topology of a remote-controlled bi-directional rotation of an A.C. fan with speed control - Boniface O. Anyaka; Princewill C. Ene; Amanze C. Fortune; Luke U. Omeje; Kenneth C. Chijioke (Institute of Advanced Engineering and Science, 2020)
The use of remote control for alternating current fans in homes/offices is one of the applications of electronics that enhances human comfort. It should therefore not be seen as luxury, rather, it should be taken as a basic requirement of life. In this study, the bi-directional rotation and speed control of ac fan were achieved using ardiuno microcontroller and tuned capacitors circuit. The use of the new state-of- the art technique in this work is significant because it helped in over-coming the drawbacks associated with the use of inductive, resistive and phase angle controlled regulators. The significance of this study will be of great benefit to physically challenged and aged persons who need to have their comforts in their various places of sitting. The designed topology of the work was executed and achieved. Reliability test carried out on the finished work showed better efficiency.